Business plasticity through disorganization - Herath, Dinuka B. (Emerald Publishing Limited, 2019)
Disorganization occurs in all areas of modern business; and yet, disorganization has traditionally been viewed as a negative factor in business and organization performance. However, in a dynamic 21st century environment our conventional structured, rigid responses in dealing with such messiness are not working. Business Plasticity Through Disorganization presents a novel approach to both academics and practitioners on how to break the shackles of rigidity and eliminate our fear of disorganization. Through a chronological discussion of the birth of the concept of 'disorganization' and its gradual evolution into 'business plasticity', the book explores ways in which embracing and leveraging messiness can help improve the way we create, innovate and run our businesses.Challenging existing theories and approaches to disorganization, as well as presenting new evidence from both research and practice, Herath promotes new conceptual thinking aimed at promoting flexible 'plasticity' in the modern organization to build greater functional capability globally.
Keywords: Organizational behavior.; Industrial organization.; Business & Economics -- Organizational Behavior.; Business & management.; elektronické knihy; electronic books